Producing ice cream with concentrated cactus pear pulp: A preliminary study - El-Samahy, S.K.; Youssef, K.M.; Moussa-Ayoub, T.E. (Journal of the Professional Association for Cactus Development, 2009)
Red cactus pear (Opuntia ficus–indica) pulp was tested for some technological and chemical characteristics. The pulp was concentrated up to 30°Brix then added at four levels (0, 5, 10 and 15%) to basic ice cream mix. The basic mix contained 0.5% gelatin, 8% fat and 10.5% milk solids non–fat (MSNF), and 16% sucrose. Some of rheological parameters of both mixes and resultant ice cream samples, in addition to some technological characteristics of resultant ice cream samples were measured. The rheological properties of all ice cream mixes before and after aging showed that the flow behavior of mixes is non–Newtonian besides being pseudoplastic behavior. While specific gravity and weight per gallon of resultant ice cream samples increased by increasing of added pulp, overrun decreased. Sensory evaluation of resultant ice cream samples showed that sample with 5% cactus was very desirable and very close to control sample. This work shows the possibility of producing a new product of ice cream using cactus pear pulp as a good fruit substitute.